Imagery Literature Study in Tennis - Bahriyanto, Ahmad (Universitas Negeri Semarang, 2023)
Imagery is one of the psychological aspects that can be used as an exercise model to improve the ability to play tennis. In the period of 5-10 training models based on imagery in the tennis game, many studies have been carried out so that it is interesting to analyze the results of research that have been made in articles and published in journals. . This study aims to review and examine the imagery training model in the tennis game which is said to improve the tennis game. The literature review that will be discussed is about the advantages of the training model in the imagery aspect of the tennis game. The results of the literature review are expected to be able to be used as studies or information that can be used as a theoretical basis for further research in training models in which there is an imagery element to be able to improve the ability to play tennis.